Cognitive Orientation to Daily Occupational Performance (CO-OP): 1-week Group Intervention with Children Referred for Motor Coordination Difficulties - Rose Martini; Jacinthe Savard (Scholarworks @ WMU, 2021)
Background: The aim of this study was to explore the effectiveness of a Cognitive Orientation to daily Occupational Performance (CO-OP) intervention delivered in a group format in a 1-week summer day camp program for children referred for motor coordination difficulties. Transfer of learned skills to self-selected tasks not addressed in the group intervention was also explored. Method: A quasi-experimental one group pretest-posttest design with a 1-month follow-up was used. Changes in nine children's self-selected occupational performance goals, as well as their sense of self-efficacy for these goals, were determined using nonparametric statistics. Results: Findings indicate a significant performance improvement at both posttest and follow-up, with large effect sizes. Self-efficacy also significantly changed across sessions on tasks directly addressed, with large effect sizes. No statistically significant changes for any of the measures were noted for the tasks that were not addressed during camp. Conclusion: The CO-OP in group format in an intensive 4-day summer day camp was effective in improving performance of self-selected camp goals, as well as self-efficacy, but less effective for transfer of learned skills to other tasks.